Phytoremediation of road salt affected soils in the Toronto region using native halophytes - Lauren Nawroth; Lyndsay A. Cartwright; Allison Rutter; Barbara Zeeb (Plant and Soil, 2025)

Zebra textures in fault-controlled, hydrothermal dolomite bodies: Coupled mechanisms of replacement, deformation, and cementation - Cole A. McCormick; Ernest H. Rutter; Hilary Corlett; Matthew Steele-MacInnis; Eivind Block Vagle; Fiona Whitaker; Cathy Hollis (Earth and Planetary Science Letters, 2025)

Evaluation of EGFR and COX pathway inhibition in human colon organoids of serrated polyposis and other hereditary cancer syndromes - Priyanka Kanth; Mark W. Hazel; John C. Schell; Jared Rutter; Ruoxin Yao; Alyssa P. Mills; Don A. Delker (Familial Cancer, 2024)
Serrated polyposis syndrome (SPS) presents with multiple sessile serrated lesions (SSL) in the large intestine and confers increased colorectal cancer (CRC) risk. However, the etiology of SPS is not known. SSL-derived organoids have not been previously studied but may help provide insights into SPS pathogenesis and identify novel biomarkers and chemopreventive strategies. This study examined effects of EGFR and COX pathway inhibition in organoid cultures derived from uninvolved colon and polyps of SPS patients. We also compared with organoids representing the hereditary gastrointestinal syndromes, Familial Adenomatous Polyposis (FAP) and Lynch syndrome (LS). Eighteen total organoid colon cultures were generated from uninvolved colon and polyps in SPS, FAP, LS, and non-syndromic screening colonoscopy patients. BRAF and KRAS mutation status was determined for each culture. Erlotinib (EGFR inhibitor) and sulindac (COX inhibitor) were applied individually and in combination. A 44-target gene custom mRNA panel (including WNT and COX pathway genes) and a 798-gene microRNA gene panel were used to quantitate organoid RNA expression by NanoString analysis. Erlotinib treatment significantly decreased levels of mRNAs associated with WNT and MAPK kinase signaling in organoids from uninvolved colon from all four patient categories and from all SSL and adenomatous polyps. Sulindac did not change the mRNA profile in any culture. Our findings suggest that EGFR inhibitors may contribute to the chemopreventive treatment of SSLs. These findings may also facilitate clinical trial design using these agents in SPS patients. Differentially expressed genes identified in our study ( MYC, FOSL1 , EGR1, IL33, LGR5 and FOXQ1 ) may be used to identify other new molecular targets for chemoprevention of SSLs.

Transcriptional response of Arabidopsis thaliana’s root-tip to spaceflight - Mohammad Shahbazi; Lindsay A. Rutter; Richard Barker (Plant Molecular Biology, 2024)

A community-level sampling method for detection of Meloidogyne enterolobii and other root-knot nematodes in sweetpotato storage roots - Julianna Culbreath; Catherine Wram; Churamani Khanal; Tyler Bechtel; Phillip A. Wadl; John Mueller; William B. Rutter (Crop Protection, 2023)

Phytotoxicity of weathered petroleum hydrocarbons in soil to boreal plant species - Prama Roy; Allison Rutter; Amy Gainer; Elizabeth Haack; Barbara A. Zeeb (Environmental Research, 2023)

An exploratory spatial contaminant assessment for polar bear (Ursus maritimus) liver, fat, and muscle from northern Canada - V Boutet; M Dominique; KM Eccles; M Branigan; M Dyck; P van Coeverden de Groot; SC Lougheed; A Rutter; VS Langlois (Environmental Pollution, 2023)

Ecological Awareness, Connection to Wetlands, and Wildlife Recreation as Drivers of Wetland Conservation Involvement - Jonathan D. Rutter; Ashley A. Dayer; Andrew H. Raedeke (Wetlands, 2022)

Correction to: Anthropogenic factors influence the occupancy of an invasive carnivore in a suburban preserve system - John P. Vanek; Andrew U. Rutter; Timothy S. Preuss; Holly P. Jones; Gary A. Glowacki (Urban Ecosystems, 2021)

Anthropogenic factors influence the occupancy of an invasive carnivore in a suburban preserve system - John P. Vanek; Andrew U. Rutter; Timothy S. Preuss; Holly P. Jones; Gary A. Glowacki (Urban Ecosystems, 2021)

The influence of Lake Erie on changes in temperature and frost dates - Kara C. Dobson; Lynne E. Beaty; Michael A. Rutter; Bryan Hed; Michael A. Campbell (International Journal of Climatology, 2020)
Anthropogenic climate change is affecting virtually all ecosystems across the globe. Some of the noticeable effects of the changing climate are the shifting of frost dates in the fall and spring, and how warm temperatures are distributed throughout the year. The degree to which an ecosystem is affected by these changes depends upon many factors, including where the ecosystem is located and what regional variabilities in climate surround that ecosystem. One ecosystem that experiences a unique microclimate is the region surrounding Lake Erie, the southernmost Laurentian Great Lake. Using historic climate data dating from 1948 to 2017, we set out to determine how changes in temperature and frost dates differ between the coastal and inland regions of the southern coast of Lake Erie, and to hypothesize as to why these effects may be occurring differently between these regions. We found that, for both coastal and inland regions, the first frost in the fall has begun later, while the last frost in the spring has begun earlier, leading to both regions experiencing longer frost‐free seasons. However, although both regions have experienced these shifts, the rate at which these shifts occurred differed between the coastal and inland regions. The average date that the frost events occurred also differs between the two regions. It was also found that average temperatures have been increasing for each region, primarily in coastal regions, due to increased minimum temperatures over time. The results from this study highlight the importance of regional climate variability in large‐scale climatic studies.

Blood lipids and colorectal polyps: testing an etiologic hypothesis using phenotypic measurements and Mendelian randomization - Michael N. Passarelli; Polly A. Newcomb; Karen W. Makar; Andrea N. Burnett-Hartman; John D. Potter; Melissa P. Upton; Lee-Ching Zhu; Michael E. Rosenfeld; Stephen M. Schwartz; Carolyn M. Rutter (Cancer Causes & Control, 2015)

Temporal and spatial patterns in tumour prevalence in brown bullhead Ameiurus nebulosus (Lesueur) in the tidal Potomac River watershed ( USA ) - A E Pinkney; J C Harshbarger; M A Rutter (Journal of Fish Diseases, 2014)
For two decades, fish tumour surveys have been used to monitor habitat quality in the Chesapeake Bay ( USA ) watershed. Tributaries with sediments contaminated with polynuclear aromatic hydrocarbons ( PAH s), known to cause liver neoplasia, were frequently targeted. Here, we compare surveys in brown bullhead Ameiurus nebulosus conducted in 2009–2011 in the tidal Potomac River watershed (including the Anacostia River) with previous surveys. Using logistic regression, we identified length and sex as covariates for liver and skin tumours. We reported a statistically significant decrease in liver tumour probabilities for standardized 280 mm Anacostia bullheads between the 1996 and 2001 samplings (merged collections: female–77.5%, male–43.0%) and 2009–2011 (female–42.2%, male–13.6%). However, liver tumour prevalence in bullheads from the Anacostia, Potomac River (Washington, DC ) and Piscataway Creek (17 km downriver) was significantly higher than that for Chesapeake Bay watershed reference locations. The causes of skin tumours in bullheads are uncertain, requiring further research. The similar liver tumour prevalence in these three locations suggests that the problem is regional rather than restricted to the Anacostia. To monitor habitat quality and the success of pollution control actions, we recommend conducting tumour surveys on a 5‐year cycle coordinated with sediment chemistry analyses.

Frequency-dependent mitochondrial Ca2+ accumulation regulates ATP synthesis in pancreatic β cells - Andrei I. Tarasov; Francesca Semplici; Daliang Li; Rosario Rizzuto; Magalie A. Ravier; Patrick Gilon; Guy A. Rutter (Pflügers Archiv - European Journal of Physiology, 2013)

Earthworm metabolomic responses after exposure to aged PCB contaminated soils - Melissa Whitfield Åslund; Myrna J. Simpson; André J. Simpson; Barbara A. Zeeb; Allison Rutter (Ecotoxicology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Effect of pumpkin root exudates on ex situ polychlorinated biphenyl (PCB) phytoextraction by pumpkin and weed species - Sarah A. Ficko; Allison Rutter; Barbara A. Zeeb (Environmental Science and Pollution Research, 2011)

Fine mapping of an epilepsy modifier gene on mouse Chromosome 19 - Sarah K. Bergren; Elizabeth D. Rutter; Jennifer A. Kearney (Mammalian Genome, 2009)

ATP depletion inhibits Ca2+ release, influx and extrusion in pancreatic acinar cells but not pathological Ca2+ responses induced by bile - Stephanie L. Barrow; Svetlana G. Voronina; Gabriela da Silva Xavier; Misha A. Chvanov; Rebecca E. Longbottom; Oleg V. Gerasimenko; Ole H. Petersen; Guy A. Rutter; Alexei V. Tepikin (Pflügers Archiv - European Journal of Physiology, 2008)

Imaging glucose-regulated insulin secretion and gene expression in single islet β-cells - Guy A. Rutter; Isabelle Leclerc; Takashi Tsuboi; Gabriela da Silva Xavier; Frédérique Diraison; Qingwen Qian (Cell Biochemistry and Biophysics, 2004)

Pathway Length and Evolutionary Constraint in Amino Acid Biosynthesis - Matthew T. Rutter; Rebecca A. Zufall (Journal of Molecular Evolution, 2004)

Imaging glucose-regulated insulin secretion and gene expression in single islet β-cells - Guy A. Rutter; Isabelle Leclerc; Takashi Tsuboi; Gabriela Silva Xavier; Frédérique Diraison; Qingwen Qian (Cell Biochemistry and Biophysics, 2004)

β-Ketoacyl-acyl carrier protein synthase III from pea (Pisum sativum L.): properties, inhibition by a novel thiolactomycin analogue and isolation of a cDNA clone encoding the enzyme - Lesley A. Jones; Andy M. Gane; Derek Herbert; David L. Willey; Andrew J. Rutter; Peter Kille; Jane E. Dancer; John L. Harwood (Planta, 2003)

Movement ofMycosphaerella fijiensis spores and sigatoka disease development on plantain close to an inoculum source - John Rutter; Peter J. A. Burt; Fernando Ramirez (Aerobiologia, 1998)

Airborne spore loads and mesoscale dispersal of the fungal pathogens causing Sigatoka diseases in banana and plantain - Peter J. A. Burt; John Rutter; Fernando Ramirez (Aerobiologia, 1998)

Changed expression of 9- O -acetyl GD3 (CDw60) in benign and atypical proliferative lesions and carcinomas of the human breast - A. Gocht; Gabriel Rutter; Bernhard Kniep (Histochemistry and Cell Biology, 1998)